2020
DOI: 10.1097/sih.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interprofessional Manikin-Based Simulation Training on Teamwork Among Real Teams During Trauma Resuscitation in Adult Emergency Departments

Abstract: This systematic review synthesizes the relevant evidence about the effectiveness of interprofessional manikin-based simulation training on teamwork among real teams during trauma resuscitation in adult civilian emergency departments. A systematic literature search was conducted in MEDLINE, CINAHL, EMBASE, EBM reviews, PsycINFO, and Web of Science with no time limit. Only experimental and quasi-experimental studies were included. Effects of the simulation intervention on teamwork were categorized according a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
7
1
Order By: Relevance
“…A team of stakeholders, including emergency department educators and the trauma program coordinator, selected interprofessional simulation training to enhance trauma team functioning. Simulation (hands-on training that allows learners to think through realistic scenarios) (Lapierre et al, 2020), when combined with interprofessional education (collaborative learning between disciplines) (Buring et al, 2009), is ideal for trauma team training.…”
mentioning
confidence: 99%
“…A team of stakeholders, including emergency department educators and the trauma program coordinator, selected interprofessional simulation training to enhance trauma team functioning. Simulation (hands-on training that allows learners to think through realistic scenarios) (Lapierre et al, 2020), when combined with interprofessional education (collaborative learning between disciplines) (Buring et al, 2009), is ideal for trauma team training.…”
mentioning
confidence: 99%
“…One observation from this review involves contrasting the attention directed toward interpersonal and cognitive skills over time. As evident in Table 2 [ 4 , 6 , 8 , 10 , 20 76 ], interpersonal skills were the exclusive focus of analyzed articles until 2007—after which articles increasingly focused on both interpersonal and cognitive skills. This expansion of focus coincides with the 2006 release of the Yule et al taxonomy [ 77 ]; however, our citation analysis found that only 5 (8%) articles [ 4 , 46 , 51 , 62 , 70 ] cited this taxonomy directly.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic reviews concluded that simulation training can have a positive impact on acquisition of non-technical skills of trauma teams, 30,31,33 but only one of them focused specifically on one type of simulation (manikin-based simulation) even though without a clear distinction between low and high-fidelity manikins. 32 Future reviews should examine the linkage of specific simulation types and competencies.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the structured list of challenges, we triangulated the data with content from relevant published literature using a backward reference tracing technique 29 (p. 353). In particular, four previous systematic literature reviews about simulation training for trauma teams were identified, [30][31][32][33] and their references were further examined to validate the identified competencies, as well as to identify suggested simulation technologies that have the potential to train the competencies. Furthermore, in order to gain an overview of recent technologies used in simulation, relevant literature was identified with a purposive sampling in MEDLINE using the search phrases: "Trauma training" AND "simulation" filtered for the years 2018-2021.…”
Section: Ethnographic Field Observationsmentioning
confidence: 99%